FREEDOM, RESPONSIBILITY, AND THE OTHER: SARTREAN EXISTENTIALISM IN MANJU KAPUR’S A MARRIED WOMAN - Singh, Neha; Singh, Krishna Murari (International Journal of Research -GRANTHAALAYAH, 2025)
Manju Kapur is mainly concerned with the existentialist predicament of her protagonists. They are tirelessly searching for their identity and make an earnest attempt to know the purpose of their existence in this universe. Man/woman is dejected to see nothing but chaos, confusion and disorder in the society in which he/she exists. Her protagonists start their journey with the freedom of choice. This study provides a detailed commentary on Manju Kapur’s A Married Woman, using existentialism, particularly Sartre’s notions of freedom, responsibility, and ‘the Other’ as a frame of reference. Existential authors like Sartre, Kierkegaard, Heidegger, Marcel, and Camus inform this study where Kapur’s heroine is placed in an existential crisis cross-and self-metamorphosis. The main character of the novel bears the burden of choice within a given structure grappling to feel deserving of unconditioned existence. The paper addresses how the heroine’s experiences epitomize existentialism, focusing on free will, human detachment, anxiety, deception, and ethics. The protagonist pursues a self-directed journey both emotionally and socially after fighting for her own agency in a heavily patriarchal and restrictive culture. This study illustrates how her self-imposed slavery of unbound-freedom came as a burden of personal responsibility.